Electrostatic Detection of Shubnikov–de Haas Oscillations in Bilayer Graphene by Coulomb Resonances in Gate‐Defined Quantum Dots. Issue 12 (30th September 2020) - Banszerus, Luca; Fabian, Thomas; Möller, Samuel; Icking, Eike; Heiming, Henning; Trellenkamp, Stefan; Lentz, Florian; Neumaier, Daniel; Otto, Martin; Watanabe, Kenji; Taniguchi, Takashi; Libisch, Florian; et al.
Abstract : A gate‐defined quantum dot in bilayer graphene is utilized as a sensitive probe for the charge density of its environment. Under the influence of a perpendicular magnetic field, the charge carrier density of the channel region next to the quantum dot oscillates due to the formation of Landau levels. This is experimentally observed as oscillations in the gate‐voltage positions of the Coulomb resonances of the nearby quantum dot. From the frequency of the oscillations, the charge carrier density in the channel is extracted, and from the amplitude the shift of the quantum dot potential. These experimental results are compared with an electrostatic simulation of the device and good agreement is found. Abstract : A gate‐defined quantum dot in bilayer graphene is utilized as a sensitive probe for the charge density of its environment. A perpendicular magnetic field is used to modulate the charge density in the channel region next to the quantum dot by forming Landau levels. The experiment is compared with an electrostatic simulation of the device.